2014
DOI: 10.1097/bcr.0b013e31828b0a46
|View full text |Cite
|
Sign up to set email alerts
|

Self-Inflicted Burns

Abstract: Suicide attempts by self-immolation are relatively rare in North America, but the physical, psychological, and social effects on the patients, families, and staff are significant. An understanding of the characteristics of the self-inflicted burn population is imperative to better inform acute, postacute, and long-term care. The goal of the present systematic review is to summarize existing literature findings on self-inflicted burns in the United States. Seven databases were searched for articles published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 41 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The self-harming behaviors often occur in the context of personality disorder or substance use disorder, or as reaction to stressful life events. [6] These conditions were ruled out after a thorough history and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The self-harming behaviors often occur in the context of personality disorder or substance use disorder, or as reaction to stressful life events. [6] These conditions were ruled out after a thorough history and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the complexity of this group of patients has a major impact on their care: Nurses who care for these patients for long periods experience increased stress and disorganization, including the fear of a new suicide attempt by the patient. 79 Honor killings, which may involve male family members setting a woman on fire as punishment for violating the family honor, are not uncommon in certain parts of the world and within certain societies and religions. 80 Inflicting burns is also sometimes used as non-religionrelated revenge.…”
Section: Self-harm and (Child) Abusementioning
confidence: 99%
“…Burns as a result of self-immolation typically lead to injuries that are larger than average and need prolonged admission times. Further, the complexity of this group of patients has a major impact on their care: Nurses who care for these patients for long periods experience increased stress and disorganization, including the fear of a new suicide attempt by the patient 79 …”
Section: Self-harm and (Child) Abusementioning
confidence: 99%
“…There are few systematic reviews and meta-analyses on suicidal burns from various parts of the world. [11][12][13][14] These reviews revealed that the highest prevalence of suicidal burns is found in South Asian and Eastern Mediterranean countries, including India, Iran, Iraq, Afghanistan and Sri Lanka. In these studies, women represent many cases of suicidal burning with high mortality.…”
Section: Open Accessmentioning
confidence: 99%